Fit-For-Purpose Cadaster Architecture for Moroccan Land-Use Planner: Proposal and Perception - Rissouni Youssef; Jamal ElHassan; Jamil Hicham; Al Ansari Rachid; El Mansouri Bouabid; Chao Jamal; Moumen Aniss (E3S Web of Conferences, 2024)
The influx of foreign investment in Morocco necessitates a robust and integrated land information system to support informed decision-making and ensure sustainable growth. The fit-for-purpose cadastre emerges as a promising solution, offering transparency, efficiency, and data-driven land management. However, its full potential remains untapped due to persistent challenges: fragmented data across government agencies, opaque information exchange mechanisms, and outdated infrastructure. This research delves into these challenges by investigating the perspectives of diverse stakeholders crucial to successful cadastre implementation: land tenure specialists, public policymakers, spatial planners, and investors. Through in-depth interviews, we illuminate the current state of land information management in Morocco, pinpoint critical roadblocks hindering transparency, efficiency, and sustainability, and propose a multi-pronged approach to unlock the transformative potential of a fit-for-purpose cadastre system.